Digital Literacy, Data Security Perception, and Behavioral Intention to Use Indonesia's Digital Identity Card (IKD): The Mediating Role of Perceived Ease of Use - Susetya Nugroho; Osly Usman (Journal of Digital Business and Global Economy, 2026)
One of the important aspects of the digital transformation agenda of Electronic-Based Government System (SPBE) in Indonesia is the Digital Identity Card (Identitas Kependudukan Digital/IKD). The distribution of its use is uneven because the urban areas are more digitally literate and the problem of personal data security remains although its use is slowly increasing in the urban areas. The research is based on the Technology Acceptance Model (TAM), and omission of the Perceived Usefulness as the mandatory and standardized usefulness of IKD, the study examines the effect of digital literacy and perception of data security on the behavioral intention of citizens to use IKD and how the perceived ease of use may mediate the relationship. A cross-sectional survey of 83 registered IKD users in DKI Jakarta, West Java and Banten was used as the data collection method and analyzed by PLS-SEM using SmartPLS 4. The common method bias was assessed by application of the single factor test and the marker-variable analysis and was found to be value of VIF which indicated no multicollinearity, SRMR = 0.071 was acceptably raised. A post-hoc power analysis provided further support of a sufficient statistical power (0.88). The results indicate that perception of data security is the most powerful predictor of the perceived ease of use (β = 0.550, p < 0.001, f² = 0.546) and behavioral intention (β = 0.351, p = 0.006). Moreover, the data security perception and behavioral intention are significantly (indirect = 0.177, p = 0.032), mediated by the perceived ease of use, but not by the digital literacy, which demonstrates a negative pattern of mediation, suggesting that the mediating process postulated by TAM is not equally effective between different antecedents. The implications of the findings on user experience design, data governance visibility, and the digital literacy policy in Indonesia and other developing economies which are undergoing digital transformation of the public services are enormous.